Identity Contingency in Ian McEwan‘s novel Atonement– A Psychoanalytic Approach - Priya, Angeline (International Journal of Psychosocial Rehabilitation, 2020)
Atonementby Ian McEwanis a successful combination of traditional realistic narrative, self-conscious devices, and deconstructionism, presented with modern experimental techniques which practically enhance its aesthetic beauty.Erikson proposed a theory of psychological and identity development that he called Psychosocial Development, which emphasizes how individual’s interactions with others influence the development of his/her identity.The protagonist (BrionyTallis) in McEwan’s Atonement experiences identity crisis, relying on the social psychologist theory of Erik Erikson.